Glomerular filtration rate measured by 99mTc‐DTPA renal dynamic imaging is significantly lower than that estimated by the CKD‐EPI equation in horseshoe kidney patients. Issue 6 (June 2016) - Qi, Yan; Hu, Panpan; Xie, Yuansheng; Wei, Kai; Jin, Meiling; Ma, Guangyu; Li, Qinggang; Xu, Baixuan; Chen, Xiangmei
Abstract: Aim: Gate's glomerular filtration rate (gGFR) measured by 99m Tc‐DTPA renal dynamic imaging and estimated GFR (eGFR) estimated by the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) equation are two indexes used to evaluate renal function. However, little is known about whether gGFR can be used to accurately assess renal function in horseshoe kidney (HSK) patients with renal fusion anomalies. Methods: Nineteen HSK patients (HSK group) diagnosed by renal imaging and 38 CKD patients with "normal kidney shape" (non‐HSK group) matched to the HSK patients in terms of gender, age and biochemical indicators at Chinese PLA General Hospital were enrolled in this study. Gender, age, serum total protein (TP), albumin (ALB), blood urea nitrogen (BUN), serum creatinine (Scr), gGFR and eGFR were recorded and analyzed using χ 2 test, t ‐test, and Wilcoxon test which was presented as median(IQR). Results: (1) There were no significant differences in gender, age, TP, ALB, BUN, Scr, or eGFR between these two groups. (2) In HSK patients, the renogram showed abnormal renal axis with the lower poles orientated medially. The timed uptake curve showed that the isotope excretion in the HSK group was slower than that in the non‐HSK group. (3) For all HSK patients, gGFR was significantly lower than eGFR (range –12.52 mL/min per 1.73m 2 to –93.18 mL/min per 1.73m 2 ). There was no significant difference in eGFR between the HSK [96.42 (36.02) mL/min per 1.73 m 2 ] and non‐HSK groups [94.46 (33.00) mL/min per 1.73 m 2 ]. The gGFR of the HSK group [41.18 (16.60) mL/min per 1.73m 2 ] was much lower than that of the non‐HSK group [86.42(26.40) mL/min per 1.73m 2, P < 0.001] and the eGFR of the HSK group ( P < 0.001). The gGFR and eGFR of the non‐HSK group were not significantly different. Conclusion: gGFR measured by 99m Tc‐DTPA renal dynamic imaging is significantly lower than eGFR estimated by the CKD‐EPI equation, which indicates that isotope renogram cannot accurately evaluate the GFR of HSK patients. Summary at a Glance: GFR determined by isotope renal dynamic imaging was compared to eGFR (CKD‐EPI) in 19 subjects with horseshoe kidneys. Isotope renograms do not accruately estimate GFR in individuals with horseshoe kidneys.